Adhatoda vasica Possesses Anti-microbial Activity and Effectively Ameliorates Ischemia Reperfusion Injury Induced by Doxorubicin through Controlling Oxidative Stress - Hershan, Almonther Abdullah; Abdulhaq, Ahmed A (Indian Journal of Pharmaceutical Education and Research, 2022)
Background and Objectives: Myocardial ischemia is one of the leading causes deaths among cardiac pathological conditions. Doxorubicin belongs to anthracycline class of drug which is effective against a wide variety of neoplasms. However, doxorubicininduced cardiotoxicity limits the clinical utility of the drug. One of the major causes of myocardial ischemia is oxidative stress. Adhatoda vasica have been shown to possess strong anti-inflammatory during ischemia reperfusion injury induced by doxorubicin in zebrafish model. Materials and Methods: Cardiac ischemia was induced in Zebrafish using doxorubicin. Adhatoda vasica was further supplemented and the antioxidants enzymes were analysed. Zebrafish was also infected with MRSA and the anti-microbial activity of A. vasica was analysed. Results: Supplementation with Adhatoda vasica extract to doxorubicin reduces the oxidative stress induced by doxorubicin through improvement of catalase, superoxide dismutase and GSH activities and subsequently reduces lipid peroxidation. Doxorubicin mediated inflammatory response in cardiac tissue is neutralized by supplementation with Adhatoda vasica plant extract and improves the cardiac tissue architecture. A. vasica plant extract is effective against inhibiting the growth of MRSA which has been shown to cause serious complications during cardiac surgery and cardiac prosthetic implantation. A. vasica plant extract causes a dose-dependent suppression of virulence gens such as spA and mecA. Conclusion: Therefore, A. vasica extract may be useful in controlling microbial infections during cardiac complications. In conclusion, the present study indicates that A. vasica can be useful during cardiac complications.
Keywords: Doxorubicin; Cardiac ischemia; Antioxidant; MRSA; Adhatoda vasica